2016
DOI: 10.1016/j.colsurfb.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

The influence of liposomal formulation on the incorporation and retention of PNA oligomers

Abstract: Liposomal formulations composed of phospholipids with different unsaturation degrees, head groups and at different cholesterol content have been tested for the encapsulation of Peptide Nucleic Acid (PNA) oligomers. The best loading capability (177μg, ER%=87.2) was obtained for pure liposomes of phosphatidylglycerol (DOPG) with negatively charged head group. The insertion of a 10-20% of cholesterol in DOPG based liposomes provides a slight decrease (∼160μg) of the PNA loading. On the other hand, the cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The addition of the DPM to the rHDL NPs greatly enhanced the EE% of the nanoparticles. The ability of DSPE-PEG to improve encapsulation efficiency and stability has also been described in other studies [83][84][85][86]. This phenomenon may be explained by the shielding effect potentiated by the PEG portion of the DSPE-PEG at the shell interface, which may help minimize the loss of payload from the nanoparticles via leakage from the core of the nanoparticles [87].…”
Section: Discussionsupporting
confidence: 54%
“…The addition of the DPM to the rHDL NPs greatly enhanced the EE% of the nanoparticles. The ability of DSPE-PEG to improve encapsulation efficiency and stability has also been described in other studies [83][84][85][86]. This phenomenon may be explained by the shielding effect potentiated by the PEG portion of the DSPE-PEG at the shell interface, which may help minimize the loss of payload from the nanoparticles via leakage from the core of the nanoparticles [87].…”
Section: Discussionsupporting
confidence: 54%
“…The encapsulation of unmodified anti-miR PNAs inside liposomal nanosystems was instead achieved and effectively used for their delivery inside K562 tumor cells [104], and a significant anti-miR effect was observed in the range 0.5-4 mM PNA concentration. Subsequently, the liposome composition was optimized by using DOPC/DOPG, cholesterol, and DSPE-PEG 2000 [105].…”
Section: Lipid and Liposome-based Approachesmentioning
confidence: 99%
“…Liposomes are the most common and clinically established vesicles for the delivery of various bio-active compounds, such as hormones, peptides, proteins, DNA, and RNA, to cells, tissues, and organs (for reviews, see [15][16][17][18]). Several studies reported the encapsulation of PNA into liposomes at neutral pH [19][20][21]. The reported PNA-containing liposomes have been internalized into human erythroleukemic cells, causing PNA-mediated reduction of microRNA (miR-210) levels in the cytoplasm [20].…”
Section: Introductionmentioning
confidence: 99%